2011
DOI: 10.1002/hep.24491
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of nonalcoholic fatty liver disease with advanced fibrosis or cirrhosis: An international collaborative study

Abstract: Information on the long-term prognosis of nonalcoholic fatty liver disease (NAFLD) is limited. We sought to describe the long-term morbidity and mortality of patients with NAFLD with advanced fibrosis or cirrhosis. We conducted this prospective cohort study including 247 patients with NAFLD and 264 patients with HCV infection that were either naïve or non-responders to treatment. Both cohorts were Child-Pugh class A and had advanced (stage 3) fibrosis or cirrhosis (stage 4) confirmed by liver biopsy at enrolme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
302
2
13

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(337 citation statements)
references
References 86 publications
(67 reference statements)
10
302
2
13
Order By: Relevance
“…[48][49][50][51][52][53] Several studies investigated the natural history of NASH cirrhosis in comparison to patients with hepatitis C cirrhosis. [54][55][56][57] One large prospective US-based study 55 observed a lower rate of decompensation and mortality in patients with NASH cirrhosis as compared to patients with hepatitis C cirrhosis. However, a more recent international study 56 of 247 NAFLD patients with advanced fibrosis and cirrhosis followed over a mean duration of 85.6 6 54.5 months showed an overall 10-year survival of 81.5% that was not different from matched patients with hepatitis C cirrhosis.…”
Section: Natural Historymentioning
confidence: 99%
“…[48][49][50][51][52][53] Several studies investigated the natural history of NASH cirrhosis in comparison to patients with hepatitis C cirrhosis. [54][55][56][57] One large prospective US-based study 55 observed a lower rate of decompensation and mortality in patients with NASH cirrhosis as compared to patients with hepatitis C cirrhosis. However, a more recent international study 56 of 247 NAFLD patients with advanced fibrosis and cirrhosis followed over a mean duration of 85.6 6 54.5 months showed an overall 10-year survival of 81.5% that was not different from matched patients with hepatitis C cirrhosis.…”
Section: Natural Historymentioning
confidence: 99%
“…Experts reviewed the data from the AARC, and the etiologic profile of cirrhosis in ACLF was found to be similar to the etiology of cirrhosis in general in the respective countries [26,46,47]. With the rising incidence of obesity and NAFLD, proportion of burnt-out NASH presenting as cryptogenic cirrhosis is also increasing [48][49][50].…”
Section: Defining the Underlying Chronic Liver Diseasementioning
confidence: 99%
“…167,168 This finding may be of potential significance in differentiating simple steatosis from NASH 167 and suggests that most hyperlipidemic patients with increased non-HDL cholesterol levels are potential candidates to liver biopsy, given that they are more likely to develop NASH. Hepatic biosynthetic failure occurring in those developing cirrhosis will blunt the severity of the initial dyslipidemia [169][170][171] mirroring the disappearance of hepatic steatosis associated with the development of NASH-cirrhosis.…”
Section: Hyperlipidemia and Hypolipidemiamentioning
confidence: 99%